Influence of injection parameters on defects formation in die casting Al12Si1,3Cu alloy: Experimental results and numeric simulation - Verran G.O.* (2006)
This paper describes the results obtained in a study performed in partnership between LabFund/DEM/PGCEM/UDESC and the WEG Motors Department of Industrial Engineering for the Quality Control and Aluminum Die Casting. It involves the combination of an experimental DOE (design of experiments) methodology and of a commercial numeric applicative. The influence of the speed injection parameters in the first and second phases and of the upset pressure over the die casting parts quality, in 305 aluminum alloys is investigated. Initially, an experiment planning was performed, where several combinations of the three injection parameters were used, in order to enable the evaluation of their influence on the occurrence of foundry defects, such as porosities and cold shuts. The obtained castings sanity evaluation was performed by visual inspections and quantitative metal graph analyses, as well as by density measurements in a significant casting region, in which great quantities of porosities appear after surface machining. In view of the obtained results, analyses were performed through numeric simulations of the die casting process, using the injection parameters for which the best and the worst results were obtained concerning the presence of porosities and cold shuts. The comparison between experimental results and the information obtained through the analyses of the performed simulations shows a good convergence, regarding the trend to porosity and cold shuts occurrence in function of the variations in the injection parameters. © 2006 Elsevier B.V. All rights reserved.